PAGI SAMPAI MALAM HARI: REPRESENTASI LATAR WAKTU DALAM CERITA ANAK INDONESIA - Apriliya, Seni; Hodidjah, Hodidjah; Kholifah, Umul (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2020)
(Title: From Morning to Night: Representation of Time Settings in IndonesianChildren's Stories). This paper aims to describe the time setting of children's stories. The study uses content analysis methods with categorization, tabulation, and inference techniques. Research data sources are 10 children's stories compiled in a book entitled